2024
DOI: 10.3390/children11020221
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictors of Long COVID in Italian Children: A Cross-Sectional Survey

Marco Schiavo,
Paola Di Filippo,
Annamaria Porreca
et al.

Abstract: Background: Identifying predictive factors of long COVID syndrome (LCS) is essential to preventing and managing this condition. We investigated the prevalence, symptoms, and risk factors of LCS in a cohort of Italian children and adolescents. Methods: We carried out a cross-sectional survey on demographic characteristics and clinical data related to COVID-19 phase and LCS in a cohort of children and adolescents, sending a questionnaire by using the PEDIATOTEM platform. Results: The prevalence of LCS was 25% (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Another common acute symptom described is headaches [5,36], which are more frequent in young people and patients with a previous diagnosis of primary headaches [37]. Indeed, in our previous publication on this survey, we found that 49.5% of COVID-19 patients complained of headaches in the acute infection, without a gender or age prevalence [20].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Another common acute symptom described is headaches [5,36], which are more frequent in young people and patients with a previous diagnosis of primary headaches [37]. Indeed, in our previous publication on this survey, we found that 49.5% of COVID-19 patients complained of headaches in the acute infection, without a gender or age prevalence [20].…”
Section: Discussionmentioning
confidence: 65%
“…Patients were divided into two age-range subgroups: 6-12 (group 1) and 13-18 (group 2). From the collected data, the first study, aimed at investigating symptoms of acute COVID-19 and Long COVID-19 with its predictive factors, was developed and published [20,21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation